Assessment of Employment Competencies from the Perspective of University Graduates : Using a Reflective Structural Equation Model - Cortejoso Lino, María; Bartolomé Muñoz de Luna, Angel; Martín Gómez, Sonia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The main objective of this research is to analyze whether the competency training of graduates of a Spanish university facilitates quality employability and student satisfaction. For this purpose, a total of 1,383 interviews were carried out between December 2023 and April 2024. This sample was evaluated using a reflexive structural equation model with Smart PLS 4, enabling the analysis of the reliability and validity of the relationships between causal variables among latent and manifest variables, as initially hypothesised. Finally, the model confirms the strength of the relationship between the dependent variable and the independent variables, settling the direct effect of employability competencies on employability, quality of employment and student satisfaction.